Genotypic distribution of multidrug-resistant and extensively drug-resistant tuberculosis in northern Thailand - Risara Jaksuwan (2018)
© 2017 Jaksuwan et al. Background: Multidrug/extensively drug-resistant tuberculosis (M/XDR-TB) is a major public health problem, and early detection is important for preventing its spread. This study aimed to demonstrate the distribution of genetic site mutation associated with drug resistance in M/XDR-TB in the northern Thai population. Methods: Thirty-four clinical MTB isolates from M/XDR-TB patients in the upper northern region of Thailand, who had been identified for drug susceptibility using the indirect agar proportion method from 2005 to 2012, were examined for genetic site mutations of katG, inhA, and ahpC for isoniazid (INH) drug resistance and rpoB for rifampicin (RIF) drug resistance. The variables included the baseline characteristics of the resistant gene, genetic site mutations, and drug susceptibility test results. Results: All 34 isolates resisted both INH and RIF. Thirty-two isolates (94.1%) showed a mutation of at least 1 codon for katG, inhA, and ahpC genes. Twenty-eight isolates (82.4%) had a mutation of at least 1 codon of rpoB gene. The katG, inhA, ahpC, and rpoB mutations were detected in 20 (58.7%), 27 (79.4%), 13 (38.2%), and 28 (82.3%) of 34 isolates. The 3 most common mutation codons were katG 315 (11/34, 35.3%), inhA 14 (11/34, 32.4%), and inhA 114 (11/34, 32.4%). For this population, the best genetic mutation test panels for INH resistance included 8 codons (katG 310, katG 340, katG 343, inhA 14, inhA 84, inhA 86, inhA 114, and ahpC 75), and for RIF resistance included 6 codons (rpoB 445, rpoB 450, rpoB 464, rpoB 490, rpoB 507, and rpoB 508) with a sensitivity of 94.1% and 82.4%, respectively. Conclusion: The genetic mutation sites for drug resistance in M/XDR-TB are quite variable. The distribution of these mutations in a certain population must be studied before developing the specific mutation test panels for each area. The results of this study can be applied for further molecular M/XDR-TB diagnosis in the upper northern region of Thailand.